Inorganic nanoparticles: Possible solution for different problems. - Benedetti, Alvise (My University, 2017)
Formation and Controlled Growth of Bismuth Titanate Phases into Mesoporous Silica Nanoparticles: An Efficient Self-Sealing Nanosystem for UV Filtering in Cosmetic Formulation. Biocompatible tailored zirconia mesoporous nanoparticles with high surface area for theranostic applications. Structural and photophysical properties of rare-earth complexes encapsulated into surface modified mesoporous silica nanoparticles
Keywords: Nanopartículas; Bismuth; Zirconia; Silica; Mesoporous nanoparticles